THE 90th ANNIVERSARY OF THE DEPARTMENT OF FRUIT CROP GENETIC RESOURCES AT VIR - A. A. Yushev (Труды по прикладной ботанике, генетике и селекции)
The article summarizes information about the 90-year activities of VIR’s Department of Fruit Crop Genetic Resources. This Department was organized at the initiative of N. I. Vavilov as the Department of Fruit Growing, Horticulture and Special Crops. Its first head was an expert in fruit crop pomology V. V. Pashkevich who later became academician. In the 1920-30s a network of experiment stations was established to grow fruit-trees, berries, nut-bearing plants, subtropical and ornamental crops, and grapes. Active plant introduction efforts were immediately launched at these stations; planting materials were imported from abroad or selected among the germplasm collected during plant explorations. Many well-known scientists contributed much to the replenishment and study of the genetic diversity of various fruit and berry plants. Among them were such Vavilov’s associates as P. N. Bogushevsky, R. P. Bologovskaya , J. F. Katz, N. I. Kichunov, N. V. Kovalev, K. F. Kostina, F. A. Kryukov, F. D. Likhonos, A.M. Negrul, N. M. Pavlova, A. M. Rozanova, G. A. Rubtsov, V. A. Rybin, G. G. Tarasenko. By 2015, the fruit crop genetic diversity at the Institute’s experiment stations reached 22 750 accessions: among them 5913 are pome plants, 7445 drupes, 4227 berries, 439 other fruits, 1587 ornamentals and 3031 grapes. Collections include wild and cultigen types, old and new cultivated varieties, sources and donors of valuable breeding and economic traits. Key words: genetic diversity, experiment stations, fruit and berry crops.